2020
DOI: 10.3390/membranes10060132
|View full text |Cite
|
Sign up to set email alerts
|

Metal Complex as a Novel Approach to Enhance the Amorphous Phase and Improve the EDLC Performance of Plasticized Proton Conducting Chitosan-Based Polymer Electrolyte

Abstract: This work indicates that glycerolized chitosan-NH4F polymer electrolytes incorporated with zinc metal complexes are crucial for EDLC application. The ionic conductivity of the plasticized system was improved drastically from 9.52 × 10−4 S/cm to 1.71 × 10−3 S/cm with the addition of a zinc metal complex. The XRD results demonstrated that the amorphous phase was enhanced for the system containing the zinc metal complex. The transference number of ions (tion) and electrons (te) were measured for two of the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 74 publications
5
37
0
Order By: Relevance
“…This indicates that the charge immigration in the SPE is mainly as a result of ions [ 60 ]. Our previous work for the glycerolized CS: NH 4 F system possesses 0.976 of t ion value, which is in good agreement with the current study [ 38 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that the charge immigration in the SPE is mainly as a result of ions [ 60 ]. Our previous work for the glycerolized CS: NH 4 F system possesses 0.976 of t ion value, which is in good agreement with the current study [ 38 ].…”
Section: Resultssupporting
confidence: 93%
“…Schematically the role of glycerol plasticizer on ion dissociation and increase of amorphous phase is shown in Scheme 1 . Earlier studies observed that upon addition of various plasticizers amorphous humps are enhanced and they attributed to the disruption of hydrogen bonds that built up the crystalline phase through the polymer host [ 29 , 32 , 33 , 38 ]. The ionic conductivity is robustly affected by the nature of crystallinity, and the amorphousness of the materials [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…This outcome is identical with the study by Lim et al [ 28 ] on PVA:LiClO 4 :TiO 2 PCE with electrochemical stability window of 2.4 V. They applied the PCE in an EDLC. The electrochemical stability window of the protonic battery is typically around 1 V [ 2 ]. Therefore, the PNCG-4 decomposition voltage reveals its suitability for the use in protonic devices.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of electrochemical and energy devices is significantly impacted by both structural and electrical properties of the used polymer electrolyte [ 45 , 46 ]. Therefore, careful selections of the host polymer with a suitable salt are the key factors in the preparation of the polymer electrolyte for practical applications.…”
Section: Introductionmentioning
confidence: 99%